Anti-neoplastic agents for patients on peritoneal dialysis: A systematic review. (June 2020) - Labaki, Chris; Rawadi, Elsa; Chebel, Roy; Bakouny, Ziad; Droz, Jean-Pierre; Kattan, Joseph G.
Highlights: Patients on peritoneal dialysis present a modified elimination of anti-cancer drugs. Oncological treatments present altered pharmacokinetics in peritoneal dialysis. Standard doses of chemotherapy cause multiple side effects in peritoneal dialysis. Dose adjustments of anti-cancer drugs in peritoneal dialysis should be considered. Abstract: Background: There is no clear consensus on the administration of anti-neoplastic agents to patients on peritoneal dialysis. Dose adjustments to prevent serious adverse events are still not established. Thus, the aim of this study was to systematically review current evidence on the use of systemic oncology therapies in peritoneal dialysis. Methods: A systematic review was conducted using PubMed, Scopus, and Cochrane. All relevant data was collected, including clinical and pharmacokinetic parameters, with comparison to subjects with normal renal function. Results: Sixteen studies were included. All were case reports. Eighteen types of anti-cancer drugs were reviewed. Multiple adverse events and altered pharmacokinetics were reported. Conclusion: Data concerning the use of anti-neoplastic drugs in patients on peritoneal dialysis are still sparse. The elimination of anti-cancer agents seems often altered in such patients, resulting in serious adverse events. Based on the available evidence, we suggest the need for dose adjustment of each drug.